Self-protected thermometry with infrared photons and defect spins in silicon carbide - Zhou, Yu (2018)
Quantum sensors with solid-state spins have attracted considerable interest due to their advantages in high sensitivity and high spatial resolution. The robustness against environmental noise is a critical requirement for solid-state spin sensors. In this paper, we present a self-protected infrared high-sensitivity thermometry based on spin defects in silicon carbide. Based on the conclusion that the Ramsey oscillations of the spin sensor are robust against magnetic noise due to a self-protected mechanism from the intrinsic transverse strain of the defect, we experimentally demonstrate the Ramsey-based thermometry. The self-protected infrared silicon-carbide thermometry may provide a promising platform for high sensitivity and high-spatial-resolution temperature sensing in a practical noisy environment, especially in biological systems and microelectronics systems.